Engineering College - Khader, Qais (My University, 2019)
This design provide to make a new imagine for the Main Function and its relation with the main circulation by rethinking of the form of the typical colleges. The Form of the college get inspired for ' Al-Aqsa Mousqe ' where they built the mosque over a big slap 'Mastaba' and all the upper Building was up of the underground structure and spaces Main concept come for the project site and typography of the project land. The proposed land is located in the city of Jerusalem, specifically in the territory of East Jerusalem, on the slope of the Mount of Olives, overlooking the Old City of Jerusalem. The high slop of the land and its Contours lines inspire the form of the college with its 'shading slices'. In order to provide a good view and ventilation for the major social Space, there is a steps of cavity in the slices until is reach the lowest level of the land, where we have the college open theater. Project doesn’t rise up from the land level ,but it engraved in the mountain under a plaza terrace , and to use this plaza we raised a two small blocks which represent the entrance including administration and library as a public functions, and under the plaza the building form is an overlapping slices in line with the mountain form, and these slices surrounds a major social space that provides visual contact with al-Aqsa mosque